THE IMAGE OF EMBRYO AND FETAL OF ETAWA CROSSBRED GOATS USING ULTRASONOGRAPHY AT DIFFERENT GESTATIONAL AGES - Juli Melia; Fauziah Fauziah; Hamdan Hamdan; Budianto Panjaitan; Syafruddin Syafruddin; Teuku Armansyah; Tongku Nizwan Siregar (Universitas Syiah Kuala, 2018)
This study aimed to estimate the gestational age of Etawa crossbred goats based on ultrasound images of embryo and fetal usingtranscutaneous ultrasonography. Etawa crossbred does (n= 5) were synchronized using double PGF2α injection with 10 days interval and matednaturally. Early pregnancy was diagnosed on 20th day after mating base on isoechogenic image of the embryo (2.65±0.75 mm) andhypoechogenic appearance of gestational sac. On 30th day of the first trimester, the embryo size was 8.31±0.42 mm. The embryo reached10.44±0.51 mm on 35th day. On 60th day, the existence of the fetal were clearly appeared along with isoechogenic of umbilical cord,hyperechogenic os cranium (25.5±0.1 mm), and body length (51.83±1.59 mm). On 75th day, the diameter of the os cranium was 33.03±0.20 mm,body length of 110±1.73 mm, and bones structures appeared hyperechogenic for os thoracalis and os vertebrae. The placenta was isoechogenoicwith diameter of 23.3±0.2 mm. On 90th day, the placenta dominated the uterus (22.67±1.70 mm) and reached its maximum diameter on 145th day(33.73±2.91 mm). In conclusion, early pregnancy detection of Etawa crossbred goats using transcutaneous ultrasonography could be performedon 20th day after mating